2015
DOI: 10.1007/s12072-015-9690-5
|View full text |Cite
|
Sign up to set email alerts
|

High FIB-4 index as an independent risk factor of prevalent chronic kidney disease in patients with nonalcoholic fatty liver disease

Abstract: High noninvasive fibrosis score is associated with an increased risk of prevalent CKD; the FIB-4 is the better predictor. With a cut-off value of 1.100 for FIB-4, it is useful in excluding the presence of CKD in patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
3
40
2
Order By: Relevance
“…Notably, in most of these studies the significant association between NAFLD and CKD persisted after adjustment for hypertension, T2DM and other known risk factors for CKD. Pan et al recently reported that after adjustment for visceral fat accumulation and other cardiometabolic risk factors, there was a positive, graded relationship between intrahepatic triglyceride content, as measured by magnetic resonance spectroscopy, and the presence of CKD or abnormal albuminuria in obese individuals 97. In a population-based study of 8270 Chinese adults with normal kidney function, NAFLD was independently associated with low levels of albuminuria also, defined as urine albumin/creatinine ratio below 30 mg/g 104.…”
Section: Epidemiological Data Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…Notably, in most of these studies the significant association between NAFLD and CKD persisted after adjustment for hypertension, T2DM and other known risk factors for CKD. Pan et al recently reported that after adjustment for visceral fat accumulation and other cardiometabolic risk factors, there was a positive, graded relationship between intrahepatic triglyceride content, as measured by magnetic resonance spectroscopy, and the presence of CKD or abnormal albuminuria in obese individuals 97. In a population-based study of 8270 Chinese adults with normal kidney function, NAFLD was independently associated with low levels of albuminuria also, defined as urine albumin/creatinine ratio below 30 mg/g 104.…”
Section: Epidemiological Data Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…It has been demonstrated that the FIB-4 score based on several laboratory tests can reliably predict advanced fibrosis and cirrhosis in NAFLD [48]. Recently, Xu et al [49] reported that a high FIB-4 score (≥1.100) is associated with an increased risk of prevalent CKD (eGFR <60 mL/min/1.73 m 2 ) and is an independent predictor of CKD in individuals with ultrasonography-diagnosed NAFLD [49]. In our study, we have first reported that urinary A1M-creatinine ratio is positively associated with the FIB-4 score and is an independent factor predicting advanced fibrosis (FIB-4 ≥1.3) in NAFLD patients with normal-range eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, a number of cross-sectional community-based and hospital-based studies have consistently demonstrated that NAFLD, as diagnosed either by imaging [16][17][18][19][20][21][22][23][24] or by histology [25][26][27][28][29] , is associated with an increased prevalence of CKD (defined as presence of decreased estimated glomerular filtration rate [eGFR] or abnormal albuminuria or overt proteinuria) in patients with NAFLD. In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Notably, in most of these studies the association between NAFLD and CKD was independent of common cardio-renal risk factors across a wide range of patient populations.…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%